Patterns of change in the justifiability of euthanasia across OECD countries - Tormos, Raül; Rudnev, Maksim; Bartolomé Peral, Edurne (Frontiers in Political Science, 2023)
Introduction The public's justifiability of euthanasia has increased as more countries have adopted laws permitting a range of end-of-life practices. Despite this trend, there is a dearth of longitudinal and comparative studies investigating attitudes toward euthanasia. Consequently, it remains unclear whether this rise in justifiability is a period-specific trend or generational change. Methods We analyzed data from the European and World Values Survey from 1981 to 2021 to examine period variations, between-cohort differences, and within-cohort changes across 35 affluent countries. This analysis was conducted using dynamic comparative multilevel regression and a comparative version of the cross-classified random effects regressions. Results Our descriptive results supported our hypotheses, indicating an increase in euthanasia's justifiability in virtually all surveyed countries, with both overall and within-cohort changes gravitating toward higher degrees of justifiability. Furthermore, newer periods and younger cohorts were found to be more permissive than their older counterparts. These consistent increases in the justifiability of euthanasia were verified by the multilevel models. Discussion Our results were in line with modernization theory, observing a gradual change in attitudes between cohorts due to generational replacement. However, we also identified intra-cohort changes related to the processes of human development across various countries. Some robustness checks produced ambiguous results in distinguishing period and cohort effects, yet the combination of these components aligns with substantive theory. Conclusion Our findings indicate a more complex pattern of change than predicted by the impressionable years model, a leading approach in political socialization research. This study contributes significantly to our understanding of evolving attitudes toward euthanasia, bridging the gap in longitudinal and comparative studies on the subject.